Level of Certain Oxidants and Antioxidants in Patients with Uterine Fibroids - Kadir Cetinkaya; Pelin Aribal Ayral; Semra Cetinkaya; Nuray Yazihan; Seyma Fadiloglu; Melahat Atasever; Ozcan Erel (Medical Network, 2019)
Objective: The mechanism of the leiomyoma formation process is still unknown. However, the menstrual cycle is associated with hypoxia, and ongoing hypoxia is associated with cellular events leading to the conversion of myometrial cells into uterine fibroids. After the hypoxic environment, the balance of cellular cytokines and growth factors changes. It was planned to evaluate the balance of oxidative agents and the role of oxidative stress in the formation of uterine fibroids. Study Design: The study was conducted in patients of gynecology outpatient clinic of Ankara Oncology Training and Research Hospital. Those volunteers with fibroids formed the study group, and the healthy ones were identified as the control group. A total of 64 subjects, 32 in both groups were included. The levels of catalase, ceruloplasmin, myeloperoxidase, native thiol, disulfide, and total thiol levels were investigated in groups. Results: Antioxidant parameters such as native thiol, disulfide, and total thiol levels were significantly decreased in uterine fibroid group. Catalase, ceruloplasmin, and myeloperoxidase levels were not statistically different between groups. Conclusion: Decrease in these antioxidant parameters showed that the hypoxia and the balance of oxidant and antioxidant substances changes may probably have associated with the pathophysiology of uterine fibroids.